(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2016)
The mouth is a promising medication delivery location because drugs taken orally bypass the digestive system and first-pass metabolism, where they might be degraded. Delivery of medications via the buccal mucosa to produce systemic pharmacological effects is what is meant by the term "buccal drug delivery."Advantages of buccalbioadhesive films over conventional dosage forms may be seen in the treatment of numerous disorders due to the controlled and gradual release of topical medications in the mouth cavity.The buccal patch is a non-dissolving, thin-matrix, modified-release dosage form designed for the supine and uncooperative patient.[1] The buccal mucosa’s accessibility, smooth, and inflexibility make it an ideal location for a bioadhesion system. Consequently, medications having a limited half life in the body. Oral flexible patches have been created to address the problems associated with taking pills. The purpose of this review is to educate readers about buccal patches and the buccal medication delivery mechanism. Review the criteria used to assess buccal patches.